2019
DOI: 10.1038/s41598-019-39579-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular origin of AuNPs-induced cytotoxicity and mechanistic study

Abstract: Gold nanoparticles (AuNPs) with diverse physicochemical properties are reported to affect biological systems differently, but the relationship between the physicochemical properties of AuNPs and their biological effects is not clearly understood. Here, we aimed to elucidate the molecular origins of AuNP-induced cytotoxicity and their mechanisms, focusing on the surface charge and structural properties of modified AuNPs. We prepared a library of well-tailored AuNPs exhibiting various functional groups and surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 74 publications
1
21
0
Order By: Relevance
“…The surface charge of NPs can regulate the oxidative stress level in cancer cells. We and other researchers have found that the intracellular ROS level is positively correlated with positively charged NPs, such as GNPs [68][69][70], polyethylenimine (PEI)-decorated GNRs [71], single-walled carbon nanotubes (SWCNTs) [72], ZnO NPs (98 nm, 11.1 mV) [73], upconversion (UCNP)@SiO 2 NPs with NH 2 decoration (37 nm, 26.2 mV) [74], and glucose-decorated iron oxide NPs (70 nm) [75]. In addition, we found that, in A549 cells, hydrophobic GNPs are more likely to induce oxidative stress than are hydrophilic NPs [68].…”
Section: The Impact Of the Nanoparticles' (Np) Physicochemical Propermentioning
confidence: 72%
“…The surface charge of NPs can regulate the oxidative stress level in cancer cells. We and other researchers have found that the intracellular ROS level is positively correlated with positively charged NPs, such as GNPs [68][69][70], polyethylenimine (PEI)-decorated GNRs [71], single-walled carbon nanotubes (SWCNTs) [72], ZnO NPs (98 nm, 11.1 mV) [73], upconversion (UCNP)@SiO 2 NPs with NH 2 decoration (37 nm, 26.2 mV) [74], and glucose-decorated iron oxide NPs (70 nm) [75]. In addition, we found that, in A549 cells, hydrophobic GNPs are more likely to induce oxidative stress than are hydrophilic NPs [68].…”
Section: The Impact Of the Nanoparticles' (Np) Physicochemical Propermentioning
confidence: 72%
“…CH-AuNPs and SC-AuNPs showed similar polydispersity (0.3 for both); however, CH-AuNPs had a positive charge (+36.7 mV) compared to a negative charge for SC-AuNPs (−10 mV). Other cationic AuNPs showed similar cytotoxicity in a cervical cancer cell line (HeLa) and in a normal human dermal fibroblast cell line (NHDF) [27]. Physicochemical properties such as surface, size, and dispersity of NPs also determine their biological impact.…”
Section: Discussionmentioning
confidence: 98%
“…The dispersity of NPs is involved in cytotoxicity, and may be related to the increase of cellular endocytosis and ROS [26]. Additionally, the interaction between cationic AuNPs and negatively charged plasma membrane were shown to be determinant for the cytotoxicity [27,28], and this positive charge of the CH-AuNPs could be also determine the selectivity to cancer cells. CH-AuNPs and SC-AuNPs showed similar polydispersity (0.3 for both); however, CH-AuNPs had a positive charge (+36.7 mV) compared to a negative charge for SC-AuNPs (−10 mV).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study showed that cytotoxicity of AuNPs is dependent on surface charge and their capacity to induce lytic interaction with the plasma membrane. Also, AuNPs interfere with cell migration, inhibit DNA replication, and promote DNA damage . Altogether these data show that more studies are necessary to better understand the cytotoxicity potential of AuNP, contributing to safe use of these NPs in nanomedicine.…”
Section: Cytotoxicity Of Aunpsmentioning
confidence: 96%